Exploring pathways to recovery and psychological well-being: examining the role of empathic and social self-efficacy, social support and social isolation - Dominguez, Maribel G.; Brown, Louis D. (Frontiers in Psychology, 2025)
BackgroundThis study examines pathways that promote psychological well-being (PWB) and recovery among mental health peer workers. Social support and social isolation are well-established predictors of PWB and recovery. One promising pathway extending from this foundation is that by building empathic and social self-efficacy, individuals can build stronger relationships, which improves social support and reduces social isolation, thereby contributing to recovery and PWB.MethodsTo test this hypothesis, we collected survey data from 268 peer workers on these constructs. We performed a continuous variable mediation analysis to predict recovery and PWB. We examined the direct and indirect effects of empathic and social self-efficacy (ESSE), with social support and social isolation as mediators in pathways toward recovery and PWB.ResultsThe direct effect of the ESSE on recovery (B = 0.30 [0.19, 0.42], p < 0.001) and PWB (B = 0.26 [0.15, 0.37], p < 0.001) was larger than the mediation effects that existed for social support when predicting PWB (B = 0.12 [0.06, 0.20], p < 0.001) and recovery (B = 0.11 [0.05, 0.19], p < 0.001). Similarly, the direct effect of social support when predicting ESSE on recovery (B = 0.36 [0.25, 0.48], p < 0.001) and PWB (B = 0.32 [0.20, 0.43], p < 0.001) was larger than its indirect effect through social isolation for both recovery (B = 0.17 [0.11, 0.24], p < 0.001) and PWB (B = 0.17 [0.12, 0.24], p < 0.001).ConclusionOur findings highlight the importance of ESSE in predicting recovery and PWB beyond what can be accounted for by social support and social isolation.